The frame-up - Bond, Gwenda (Del Rey, an imprint of Random House, 2024)
"Dani Poissant is the daughter and former accomplice of the world's most famous art thief. There was no job too big for Maria and her loyal crew. The secret to their success? A little thing called magic, kept rigorously secret from the non-magical world. They seemed unstoppable... until a teenage Dani turned her mother over to the FBI. Ten years later, with Maria still in prison, Dani finds herself approached for a job that only Maria and her crew could pull off... if any of them were still speaking to her. But it's the job of a lifetime and it might just be the lure Dani needs to reconcile with her mother and be reunited with her old gang - including both the love of her life and her former best friend. The problem is, it's an impossible task - even with the magial talents of the people she once considered family baking her up. It's a heist that needs a year to plan, and Dani has just over a week. Worse, the more ani learns, the more she understands there's far more at stake in this job than she ever realized." -- Back cover.